2011
DOI: 10.1080/13540602.2011.538499
|View full text |Cite
|
Sign up to set email alerts
|

Better serving the needs of limited English proficient (LEP) students in the mainstream classroom: examining the impact of an inquiry‐based hybrid professional development program

Abstract: In this study, the authors examine the impact of an English as a second language (ESL) professional development offering designed to meet this challenge: the Modular Design for English Language Learners (MODELL) instruction program. The authors were part of a team of faculty that designed and developed this hybrid professional development program to support classroom teachers challenged with assessing and addressing the educational needs of limited English proficient (LEP) students. The authors theorize that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The findings reported in this paper support some earlier research suggesting that many mainstream teachers perceive that they are ill-prepared to work with ELLs (Evans, ArnotHopffer, & Jurich, 2005;Hutchinson & Hadjioannou, 2011;Reeves, 2006;Siwatu, 2011;Webster & Valeo, 2011). This study builds upon this research by considering the role identity construction can play in the perceptions' of preservice mainstream teachers about their preparedness to teach ELLs.…”
Section: Conflict and Identity Constructionsupporting
confidence: 72%
“…The findings reported in this paper support some earlier research suggesting that many mainstream teachers perceive that they are ill-prepared to work with ELLs (Evans, ArnotHopffer, & Jurich, 2005;Hutchinson & Hadjioannou, 2011;Reeves, 2006;Siwatu, 2011;Webster & Valeo, 2011). This study builds upon this research by considering the role identity construction can play in the perceptions' of preservice mainstream teachers about their preparedness to teach ELLs.…”
Section: Conflict and Identity Constructionsupporting
confidence: 72%
“…This act of synthesising notes from a planning meeting was another opportunity for teacher reflection and learning as both teachers made sense of what they were planning to teach and considered how this would be communicated with others at the school. Teachers explained that email was easily shared with others in the school, which raised awareness of ESOL issues and their co-teaching practices across the school, creating an expanded activity network of support (Hutchinson & Hadjioannou, 2011).…”
Section: Using Tools To Communicate and Make Sense Of Teaching Goalsmentioning
confidence: 99%
“…As the population of culturally and linguistically diverse students continues to increase in schools around the world, research has shown that many teachers are not adequately prepared to meet the needs of these students (Gándara, Maxwell-Jolly, & Rumberger, 2008;Haworth, 2008;Hutchinson & Hadjioannou, 2011;Miller, 2011;Rumberger & Gándara, 2005;Téllez & Waxman, 2006). This situation presents a challenge and an opportunity to engage teachers in ongoing learning in their schools as they seek better ways to teach language minority students (we use the term English language learners, or ELLs, throughout this paper because this was the term used in the school context), yet more research is needed to understand how to promote this learning among teachers.…”
Section: Introductionmentioning
confidence: 98%
“…Researchers in education and language teaching have shown that many educators are not adequately prepared to teach culturally and linguistically diverse students (Gay, 2002;Hutchinson & Hadjioannou, 2011;Verdugo & Flores, 2007;Echevarria, Vogt, & Short, 2007). Empirical studies have indicated that English language learners (ELLs) continue to academically lag behind their native English-speaking peers.…”
Section: Introductionmentioning
confidence: 99%